2019
DOI: 10.1039/c9tc00554d
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast laser pulse (115 fs) generation by using direct bandgap ultrasmall 2D GaTe quantum dots

Abstract: Mode-locked ultrashort-pulse lasers are obtained by using direct bandgap GaTe quantum dots as a new saturable absorber. The pulse duration obtained is 115 fs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The slope efficiency of fiber laser depends on the efficiency of the gain medium and the loss of a laser cavity. The Stokes limit of a Yb‐doped fiber is higher than that of an Er‐doped fiber, [ 25 ] which leads to Yb‐doped fiber having higher skew efficiency. The maximum single pulse energy and peak power at the pump power of 500 mW are 0.842 nJ and 4.63 W, respectively.…”
Section: Ultrafast Photonics Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slope efficiency of fiber laser depends on the efficiency of the gain medium and the loss of a laser cavity. The Stokes limit of a Yb‐doped fiber is higher than that of an Er‐doped fiber, [ 25 ] which leads to Yb‐doped fiber having higher skew efficiency. The maximum single pulse energy and peak power at the pump power of 500 mW are 0.842 nJ and 4.63 W, respectively.…”
Section: Ultrafast Photonics Applicationsmentioning
confidence: 99%
“…[23] So far, QDs have been used in photoluminescence, photocatalysis, and energy conversion because of their unique quantum confinement effect. [24,25] Up to now, a variety of QD materials have been proven to be SAs to generate ultrafast and ultranarrow pulses, such as carbon QDs, [26] BP QDs, [27] and PbO QDs. [28] Although there have been many reports of MXene nanosheets being used as SAs to generate ultrafast pulses, no reports of MXene QDs in the direction of ultrafast pulses have been found.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that QDs have gained a marked interest for their promising prospects in nonlinear optics during the past two years. The enhanced nonlinear effects caused by quantum confinement effects [36,37] promote the development of QDs SA. It has been observed that ultrafast pulses were generated relatively easily for Ti 3 C 2 T x QDs compared with Ti 3 C 2 T x nanosheets (NSs) [27,29].…”
Section: Introductionmentioning
confidence: 99%
“…observed the SA property of NbSe 2 and GaTe QDs by demonstrating the generation of ultrafast laser pulses in both Er‐doped and Yb‐doped laser cavity, respectively. [ 19,20 ] Recently, QDs based on group II–VI chalcogenides (cadmium sulfide, CdS; cadmium selenide, CdSe) and group IV–VI chalcogenides (lead sulfide, PbS) have been introduced as SAs in the fiber laser system, and the generation of ultrafast laser pulses has been demonstrated. [ 21–23 ] However, Pb‐ and Cd‐based QDs are toxic heavy metals that might pose significant risks to the environment.…”
Section: Introductionmentioning
confidence: 99%